Agronegócio no Mato Grosso: impactos da cultura do algodão no território de Lucas do Rio Verde - Dentz, Marizete Von (2019)
Considering that agricultural production in Brazil, mainly in the state of Mato Grosso, region of the agricultural fronts, has been attracting global investments due to the deepening of the energy transition, the demand for food in the world and changes in the modes of consumption, our objective in this research , is to investigate and analyze the new territorialization of cotton production in the state of Mato Grosso, with focus on the municipality of Lucas do Rio Verde, with changes occurring from the 1990s, propitiated by technical-scientific-informational innovations. For the purposes of a broader investigation, the evolutionary process of the modernization of Brazilian agriculture and its geoeconomic repercussions in the geographic space of the country was taken as problematization. Methodologically, the research carries out a theoretical immersion in the surroundings of the referended territory as well as of the cotton culture and for closer approximation we seek through the instruments of the semistructured interview, the accomplishment of the field work with the cotton growers, as well as other organizations that foment this discussion. In addition, it is important to point out that part of the cotton produced in the state of Mato Grosso is exported to other countries, in order to sustain the economic dynamics of agribusiness and provide raw material for areas lacking this agricultural product. Thus, investment in the cotton crop is not only another lucrative opportunity integrated into soybeans, corn and beef cattle for the producers of Mato Grosso. Also an attractive crop, for the post-harvest time of soybeans, even though it is a sensitive and high-cost crop and risks, cotton growers concentrate their financial capital, aided by an interconnected system of credit, specialized labor and product processing for export. In view of the proposal we present Lucas do Rio Verde - MT, as an integral part of the agribusiness of the state as well as nation, contributing significantly to the productive dynamics of cotton growing, meeting the national and international demands.